Cell wall organic matrix composition and biomineralization across reef‐building coralline algae under global change. Issue 1 (22nd November 2022) - Bergstrom, Ellie; Lahnstein, Jelle; Collins, Helen; Page, Tessa M.; Bulone, Vincent; Diaz‐Pulido, Guillermo
Abstract : Crustose coralline algae (CCA) are one of the most important benthic substrate consolidators on coral reefs through their ability to deposit calcium carbonate on an organic matrix in their cell walls. Discrete polysaccharides have been recognized for their role in biomineralization, yet little is known about the carbohydrate composition of organic matrices across CCA taxa and whether they have the capacity to modulate their organic matrix constituents amidst environmental change, particularly the threats of ocean acidification (OA) and warming. We simulated elevated p CO2 and temperature (IPCC RCP 8.5) and subjected four mid‐shelf Great Barrier Reef species of CCA to 2 months of experimentation. To assess the variability in surficial monosaccharide composition and biomineralization across species and treatments, we determined the monosaccharide composition of the polysaccharides present in the cell walls of surficial algal tissue and quantified calcification. Our results revealed dissimilarity among species' monosaccharide constituents, which suggests that organic matrices are composed of different polysaccharides across CCA taxa. We also observed that species differentially modulate composition in response to ocean acidification and warming. Our findings suggest that both variability in composition and ability to modulate monosaccharide abundance may play a crucial role in surficial biomineralization dynamics under the stress of OA and global warming.